An empirical comparative study on the diagnostic index system for techniques and tactics in men's table tennis during the ABS plastic ball era - Xu, J.; Wang, Q.; Marchibayeva, U.; Bolat, N.; Sagidolla, M.; Kalym, Y.; Aidarkhan, K.; Alam, J.; Zhalel, A. (Frontiers in Sports and Active Living, 2025)
In order to accurately identify the diagnostic index system that can best reflect the technical and tactical performance of table tennis after the implementation of the new ABS material ball, and then more accurately and efficiently diagnose and analyze the technical and tactical ability of players. This paper uses the methods of match observation, mathematical statistics, literature and other methods to carry out an empirical comparative study on the representative segmented diagnostic indicator system constructed by predecessors in the past 20 years. Research suggests that: 1) in the New Ball Era, each segmented diagnostic indicator system has a certain degree of rationality, but in comparison, the five-segment diagnostic indicator system is the most optimal and the most accurate to reveal the technical and tactical performance in the new era. 2) The five segments consist of the serving-attacking segment, receiving-attacking segment, serving-attacking connection segment, receiving-attacking connection segment, and the sustaining segment. 3) The impact of these five segments on the outcome of the match is as follows: The "attacking" segments have the greatest impact on the match outcome, followed by the "connecting" segments, and the "sustaining" segment has the smallest impact. The impact of the receiving and attacking segment on the outcome of the match is higher than that of the serving and attacking segment, and the impact of the serving and attacking connection segment on the outcome of the match is higher than that of the receiving and attacking connection segment. 4) In the New Ball Era, the fifth and sixth strokes of the "connecting" segment have gained prominence, playing a pivotal role for transitioning between offense and defense in the "attacking" segment and the "sustaining" segment. These findings highlight the need for coaches and analysts to adopt the five-segment diagnostic indicator system as a more accurate framework for evaluating performance. Emphasizing training in the receiving-attacking and connecting phases - especially the fifth and sixth strokes, can provide a competitive edge under the dynamics of the New Ball Era. This refined understanding can guide more targeted technical and tactical preparation, better aligning training priorities with the actual determinants of match outcomes.